Opium Alkaloids in Harvested and Thermally Processed Poppy Seeds - Carlin, Michelle G.; Dean, John R.; Ames, Jennifer M. (Frontiers in Chemistry, 2020)
The opium alkaloids morphine, codeine, thebaine, noscapine and papaverine have been detected on poppy seeds; they are widely used by the food industry for decoration and flavor but can introduce opium alkaloids into the food chain. Of the opium alkaloids found on poppy seeds, morphine and codeine are the most pharmacologically active and have been detected in biological matrices collected in workplace and roadside drug testing resulting in positive opiate results. The European Food Safety Authority introduced an acute reference dose of 10 μg morphine / kg of body weight as a safe level for morphine in food products. In this work, it was found that in harvested poppy seeds, and thermally processed poppy seeds (with and without a food matrix), if used in normal levels would not exceed the recommended acute reference dose. It was also shown that the levels of all alkaloids reduce when thermally processed, in comparison with harvested, untreated seeds.